Organoleptic rating of various value added products of unripe mango cv. Rajapuri (Indian Journal of Arid Horticulture, 2025)
Mango (Mangifera indica L.) cv. Rajapuri is the most important and unique commercial fruit for processing industries. The demand of mango fruit fresh as well as processed products increase day by day because its excellent flavor, attractive fragrance, beautiful shades of color, delicious taste and high nutritive value. Mango processing is big industries which use both ripe and unripe fruits. Unripe fruits are used for preparation for chutney (salt or sugar added), pickle, amchur, mango pulp vegetable, green mango drink (panna) etc. The variety Rajapuri is originated and grown on large scale in this region and used as processed products. The recipe and methods used for preparation of various products are varying according to place to place and taste of consumer. The Panchmahals district of Gujarat is tribal dominant area. In the district mango is of time position in area (2200 ha.) as well as production (13200 MT) Anonymous (2011). The tribal used it for preparation of various products, but the products prepared by them spoil early. So, that the present study was carried out on preparation on various mango products and their organoleptic taste for tribal's of the area. To see the taste of consumer and make them understand through various extension tools like training, demonstration, advisory service, etc. for preparation of various products and how to increase the shelf life of products.
Keywords: demonstration; nutritive; Mangifera indica L; Anonymous; tribal; organoleptic